Therapeutic hypothermia for neonatal encephalopathy in low- and middle-income countries: a systematic review and meta-analysis. - Shreela S Pauliah; Seetha Shankaran; Angie Wade; Ernest B Cady; Sudhin Thayyil (PLoS ONE, 2013)
Unlabelled Although selective or whole body cooling combined with optimal intensive care improves outcomes following neonatal encephalopathy in high-income countries, the safety and efficacy of cooling in low-and middle-income countries is not known. Objective We performed a systematic review and meta-analysis of all published randomised or quasi-randomised controlled trials of cooling therapy for neonatal encephalopathy in low-and middle-income countries. Results Seven trials, comprising a total of 567 infants were included in the meta-analysis. Most study infants had mild (15%) or moderate encephalopathy (48%) and did not receive invasive ventilation (88%). Cooling devices included water-circulating cooling caps, frozen gel packs, ice, water bottles, and phase-changing material. No statistically significant reduction in neonatal mortality was seen with cooling (risk ratio: 0.74, 95% confidence intervals: 0.44 to 1.25). Data on other neonatal morbidities and long-term neurological outcomes were insufficient. Conclusion Cooling therapy was not associated with a statistically significant reduction in neonatal mortality in low-and middle-income countries although the confidence intervals were wide and not incompatible with results seen in high-income countries. The apparent lack of treatment effect may be due to the heterogeneity and poor quality of the included studies, inefficiency of the low technology cooling devices, lack of optimal neonatal intensive care, sedation and ventilatory support, overuse of oxygen, or may be due to the intrinsic difference in the population, for example higher rates of perinatal infection, obstructed labor, intrauterine growth retardation and maternal malnutrition. Evaluation of the safety and efficacy of cooling in adequately powered randomised controlled trials is required before cooling is offered in routine clinical practice in low-and middle-income countries.